MgFe2O4 Magnetic Catalyst for Photocatalytic Degradation of Congo Red Dye in Aqueous Solution Under Visible Light Irradiation: 10.32526/ennrj/21/20230002 - Riyanti, Fahma; Nurhidayah, Nurhidayah; Purwaningrum, Widia; Yuliasari, Nova; Hariani, Poedji Loekitowati (Environment and Natural Resources Journal, 2023)
In this study, MgFe2O4 was successfully synthesized through the coprecipitation method using the precursors Fe(NO3)3·9H2O and Mg(NO3)2·6H2O. The MgFe2O4 product was characterized using XRD, SEM-EDS, VSM, UV-DRS, and FTIR. The catalyst was used for the photocatalytic degradation of Congo red dye under visible light irradiation. The variables of the photocatalytic degradation included solution pH, Congo red concentration, H2O2 concentration, and irradiation time. The MgFe2O4 synthesized has magnetic properties, with a saturation magnetization value of 17.78 emu/g and a band gap of 1.88 eV. A degradation efficiency of 99.62% was achieved under specific conditions, including a Congo red concentration of 10 mg/L, a solution pH of 6, an H2O2 concentration of 2.5 mM, and an irradiation time of 180 min. The degradation efficiency without H2O2 was observed to be 83.45%. The photocatalytic degradation of Congo red followed the pseudo-first-order kinetics model with a rate constant (k) of 0.0167 min-1 and a half-life (t1/2) of 41.49 min. The total organic carbon (TOC) removal of 84.58% indicated that the mineralization of Congo red had occurred. The effectiveness of photocatalytic degradation decreased from 99.62% to 94.50% (<5%) after five cycles of photocatalytic degradation. The results demonstrated that MgFe2O4 has a high Congo red dye degradation efficiency, can be regenerated, and is readily separated from the solution using a permanent magnet.